The lost man [compact disc, unabridged] - Harper, Jane (Jane Elizabeth) (Macmillan Audio, 2019)
"Two brothers meet at the remote fence line separating their cattle ranches in the lonely outback. In an isolated belt of Queensland, they are each other's nearest neighbor, their homes four hours' drive apart. The third brother lies dead at their feet. Something caused Cam, the middle child who had been in charge of the family homestead, to die alone in the middle of nowhere. So the eldest brother returns with his younger sibling to the family property and those left behind. But the fragile balance of the ranch is threatened. Amidst the grief, suspicion starts to take hold, and the eldest brother begins to wonder if more than one among them is at risk of crumbling as the weight of isolation bears down on them all." -- Amazon.